Molecular Exploration of Guava (Psidium guajava L.) Genome Using SSR and RAPD Markers: A Step towards Establishing Linkage Map - B Padmakar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
In the present study, molecular evaluation of two guava mapping populations (MP), MPI comprising 94 F1 progenies and MPII comprising 46 F1 progenies, was carried out using simple sequence repeat (SSR) and random amplified polymorphic DNA (RAPD) markers. A pseudo-test cross strategy was implemented where 'Kamsari' X 'Purple Local' and 'Purple Local' X 'Allahabad Safeda' were crossed, and, these showed variation in fruit quality traits such as seedstrength (hardness/softness), fruit weight, TSS and pulp color. A set of 30 RAPD markers was used for genotyping MPI while a set of 55 SSR markers was used for genotyping MPII. In case of MPI, 30 RAPD markers generated 214 scorable markers, of which 80 markers were specific to 'Kamsari', 14 markers to 'Purple Local' and the remaining 120 were intercross markers. As for MPII, 55 polymorphic SSR markers resulted in generation of 207 alleles (with a maximum of 4 alleles and a minimum of 3 alleles per locus), of which 108 alleles were specific to 'Purple Local' while 99 were specific to 'Allahabad Safeda'. Genotypic data thus generated can be further exploited for constructing genetic linkage maps and mapping complex QTLs governing fruit quality traits in guava..